Investors’ Perception Towards Capital Market – An Empirical Study With Reference to Sivakasi, Tamil Nadu - Palaneeswari, T.; Kaleeswari, J. (Indian Journal of Finance, 2011)
The Indian capital market is one of the oldest and largest capital markets of the world. The rapid industrialization in the country since independence has given vitality to the capital market. Savings of the household sector can be directly channelized into the corporate sector, that will facilitate the development of industrial and service sectors. This requires the existence of an efficient capital market, through which, small and scattered savings of investors are directed into productive activities of corporate enterprises. The first instance of organized trading of securities in India was started by the East India Company in the 19th century. The establishment of Bombay Stock Exchange was the first in India, which was started early in 1875, and, which gave momentum to the capital market operations in the country. The market reforms initiated as part of liberalization measures in the nineties added vigor to the growth of the Indian capital market. The aggregate volume of trade, market capitalization and the number of listed companies of these stock exchanges are comparable to world standards. However, investors are experiencing a number of grievances from different market participants. Their widespread geographical distribution, unorganized nature and lack of awareness about capital market investment have instigated unscrupulous market participants to exploit them. This calls for the attention of the Government and other policy makers to take initiatives to overcome the problems and to make steps to invite the proposed investors into the security market to pave way for the individual development, thereby improving the economy of the nation. Securities market is regulated by Securities and Exchange Board of India (SEBI). Hence, an attempt was made to know the perception of the investors’ awareness, investment option, purpose of investment, factors influencing investment in the capital market, etc. For this study, investors’ opinions were collected and the data was analyzed to determine awareness and perception of people towards capital market investments in Sivakasi Town, Tamil Nadu.